(3GdehLR aj GdWHs - (3GHf GdfajS , YdGA GdOjf CHh GdMSf Ydj Hf CHj GdMRe GdbQTj, GHf GdfajS,J (B687 (3g` s ((3ejNGFjd UhGHg WHjH s)
(3ChdgG (B:s
(3LdGH jUQa GdShS hbdjd NHR Ke EeQGb GdaQGjL Ch eQbI GdOjc hNUhUkG GdgQe s
(3BNQgG (B:s
(3hjCcd fUa GdfgGQ CSajO HGO HdM GdeaQi hjTQH GdfHjP GdUQa eOI CSHhY Ch ESHhYjf bO Je gPG GdcJGH HYhf YfGjI Gdedc GdhgGH s
(3HgG fXGe GdJYbjHIs
(3fSNJ SfI (B1865(3es
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B58s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1899s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs